Newnes interfacing companion - Fischer-Cripps, Anthony C. (Oxford ; Boston : Newnes, 2002)
Tony Fischer-Cripps is a Project Leader in the Division of Telecommunications and Industrial Physics of the CSIRO (Commonwealth Scientific & Industrial Research Organisation), Australia. He was previously lecturer, University of Technology, Sydney (UTS), Australia, and has also worked for the National Institute of Standards and Technology, USA (NIST, formerly National Bureau of Standards - NBS). *The essential pocket reference for engineers and students *Interfacing in action: PCs, PLCs, transducers and instrumentation in one book *Develop systems and applications that work with Newnes Interfacing Companion.
Transducers -- Interfacing -- Signal processing.
Includes bibliographical references (p. 294) and index.
Keywords: Transducers; Computer input-output equipment; Signal processing; Electronic books